Direct observation of chemical short-range order in 25 wt% Mn steel via transmission electron microscopy. (May 2022) - Kayani, Saif Haider; Park, Sangeun; Kim, Jung Gi; Seol, Jae Bok; Sung, Hyokyung
Abstract: In this study, we demonstrate the existence of chemical short-range order (CSRO) in high-Mn (25Mn-0.6C-Fe in wt%) austenitic steel. A definitive proof of CSRO was obtained by electron diffraction measurements and dark-field imaging via transmission electron microscopy. CSRO in the steel sample generated additional diffuse scattering in selected area electron diffraction patterns along high-index zone axes, namely, [1 1 1]γ, [1 1 2]γ, and [1 3 0]γ, which was absent along low-index zone axes, namely, [1 1 0]γ and [0 0 1]γ . We found that CSRO induced lattice distortions, and the corresponding interplanar spacing was twice that in γ-austenite. This study offers a useful approach to detect CSRO in other high-Mn steels. Graphical abstact: Image, graphical abstract